Reducing Cultural Gap through Variation in Language Choice as an Acculturation Strategy for Sasak Immigrants @InaqGrace - Fahad, Malik; Kurniasih, Baiq Rahayu; Putri, Latifah Rahmadani (Research Community for Critical Society and Environment, 2025)
Cross-border movements can pose challenges for immigrants as they adapt to the host society's culture and language. This study focuses on Inaq Grace's language choice as an acculturation strategy in Lombok, Indonesia, including patterns of variation, language choice, and influencing factors. This study uses Berry's (1992) theory of acculturation strategies and Fishman's (1972) theory of domains of language use. As a data source used by YouTube, there are five videos, one of which is the speech of the @InaqGrace account uploaded in 2021. First, the data collection stage uses the listening and note-taking method. This method involves transcribing, classifying, and recording the utterances from the @InaqGrace account. The result reveals that Grace communicates in a variety of languages while in Lombok, including Sasak, Indonesian, and English. It reflects communication in social contexts, comprising the variety of languages spoken in Indonesia, including local, foreign, and Indonesian languages. Variations in language choice used by Grace in her activities while living on the island of Lombok in the video are communicating in the realms of shopping, friendship, religion, and neighbourliness. These factors include the participants involved, depending on the topic and function of communication, the habitual factor of hearing or using the language, and the preservation of the language being used.